THE RELATIONSHIP BETWEEN TEACHER TEACHING STYLE AND STUDENTS' LEARNING MOTIVATION IN LEARNING ENGLISH AT TENTH GRADE OF SMA NEGERI 1 SIANTAR PERUMNAS BATU VI - Gabriella Clarisa Silaban; Yanti Kristina Sinaga; Mungkap Mangapul Siahaan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to write the relationship between teacher teaching styles and student learning benefits in the English division of class X of SMA Negeri 1 Siantar Perumnas Batu VI. This study is based on Grasha's (1996) teaching style theory, especially the facilitator teaching style, as well as the concept of learning motivation according to Sanchez-Boliver & Martinez-Martinez (2022) which emphasizes intrinsic motivation as a driver of student engagement. This study uses a quantitative descriptive correlational design. The study population was all class X students, while the sample was taken purposively from class X-2 which amounted to 36 students and 1 English teacher at SMA Negeri 1 Siantar Perumnas Batu VI. The research instrument was a questionnaire with a Likert scale, then the data were analyzed using the Person Product Moment correlation test through the SPSS program. The results of the study showed that there was a significant positive relationship between teacher teaching styles and student learning motivation with a correlation coefficient value of r = 0.537 and a significance of p = 0.000 (p <0.05). This indicates that the more appropriate the facilitator teaching style applied by the teacher, the higher the student's motivation in learning English. Researchers concluded that a facilitator's teaching style plays a crucial role in increasing student learning motivation. Therefore, teachers are advised to adopt a teaching style that focuses on student guidance, interaction, and independence to create a more engaging and motivating learning environment.